Forming a national community of practice of food system planning initiatives aligned with the United Nations Sustainable Development Goals - Konstantinos Zougris; Albie F. Miles; Rose Benjamin; Ella Geismar (Frontiers in Sustainable Food Systems)
IntroductionThis paper is designed to identify key factors informing the process of developing a United States-based national community of practice of state and regional food system planning efforts aligned with the United Nations Sustainable Development Goals.MethodsGrounded in an extensive literature review, we employed an exploratory sequential mixed methods design to assess the needs, functions, challenges, and likelihood for participation in a national community of practice aligned with the United Nations Sustainable Development Goals. Data drawn by a series of semi-structured interviews with 25 leading experts, complemented by a set of self-administered online surveys of 35 practitioners of food planning efforts across the nation.ResultsOur integrative findings revealed overwhelmingly interest and need for the development of a national community of practice aligned with the United Nations Sustainable Development Goals. The findings further indicate that in the process of developing a national community of practice, the principles and functions of shared governance, mutual trust and collective fundraising are essential to supporting credible and coordinated activities that promote equity, reinforce capacity building, promote research on food system measurements, and strengthen advocacy for systemic transformation aligned with the UN Sustainable Development Goals. Finally, our study revealed a rampant interest in collaboration and knowledge sharing in various stages of the formation of a national community of practice. The majority of the participants appear to be familiar, yet only a small fraction of their organizations appear to be formally aligned with the UN Sustainable Development Goals.DiscussionOur integrative findings emerge with Wenger’s conceptual framework offering a suitable theoretical grounding in the process of developing a community of practice in food systems planning. The implication of this study denotes the importance of collaboration among academic research institutions, legislators and FPEs within the community that can spur adaptation, innovation, and integration in food system planning, policy, implementation, and monitoring. Coordination in pooling resources and aligning efforts can lead to more efficient use and allocation of funds, ensuring that investments are directed toward the most impactful practices aligned with state and regional food system initiatives and planning efforts.